Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: Ta có: 7x+6(3-x)=27-20+73
\(\Leftrightarrow7x+18-6x=80\)
\(\Leftrightarrow x=80-18=62\)
Vậy: x=62
2: Ta có: \(6x-5\left(x-7\right)=\left(27-514\right)-486-73\)
\(\Leftrightarrow6x-5x+35=27-514-486-73\)
\(\Leftrightarrow x+35=-1046\)
\(\Leftrightarrow x=-1081\)
Vậy: x=-1081
1: =>|x-5|=5-7x+7x+28=33
=>x-5=33 hoặc x-5=-33
=>x=38 hoặc x=-28
3: 2|x-6|+7x-2=|x-6|+7x
=>|x-6|=2
=>x-6=2 hoặc x-6=-2
=>x=8 hoặc x=4
\(1,\\ a,=7x^3-49x^2+21x\\ b,=x^2-x-42\\ c,=x^2-16x+64\\ d,=9x^2+12x+4\\ e,=x^2-16-25+10x-x^2=10x-41\\ 2,\\ a,\Rightarrow2\left(x-7\right)=19\\ \Rightarrow x-7=\dfrac{19}{2}\Rightarrow x=\dfrac{33}{2}\\ b,\Rightarrow4x^2-20x+25-4x^2+3x-2x=50\\ \Rightarrow-19x=25\Rightarrow x=-\dfrac{25}{19}\)
\(3\cdot\left(\dfrac{1}{2}-x\right)-5\left(x-\dfrac{1}{10}\right)=-\dfrac{7}{4}\\ \Leftrightarrow-8x=-\dfrac{15}{4}\\ \Leftrightarrow x=\dfrac{15}{32}\)
\(4\left(\dfrac{3}{4}+x\right)-\dfrac{1}{5}=7x-\dfrac{1}{7}\\ \Leftrightarrow3x=\dfrac{103}{35}\\ \Leftrightarrow x=\dfrac{103}{105}\)
\(3\left(\dfrac{1}{2}-x\right)-5\left(x-\dfrac{1}{10}\right)=-\dfrac{7}{4}\)
\(\Rightarrow\dfrac{3}{2}-3x-5x+\dfrac{1}{2}=-\dfrac{7}{4}\)
\(\Rightarrow2-8x=-\dfrac{7}{4}\)
\(\Rightarrow8x=2+\dfrac{7}{4}\)
\(\Rightarrow8x=\dfrac{15}{4}\)
\(\Rightarrow x=\dfrac{15}{32}\)
___________
\(4\left(\dfrac{3}{4}+x\right)-\dfrac{1}{5}=7x-\dfrac{1}{7}\)
\(\Rightarrow3+4x-\dfrac{1}{5}=7x-\dfrac{1}{7}\)
\(\Rightarrow4x+\dfrac{14}{5}=7x-\dfrac{1}{7}\)
\(\Rightarrow7x-4x=\dfrac{14}{5}+\dfrac{1}{7}\)
\(\Rightarrow3x=\dfrac{103}{35}\)
\(\Rightarrow x=\dfrac{103}{105}\)
`a,4x-10=0 `
`<=> 4x=10`
`<=>x=10/4`
`<=>x=5/2`
`b, 7-3x=9-x `
`<=>-3x+x=9-7`
`<=>-2x=2`
`<=>x=-1`
`c, 2x-(3-5x) = 4(x+3)`
`<=>2x-3+5x=4x+12`
`<=>2x+5x-4x=12+3`
`<=>3x=15`
`<=>x=5`
`d, 5-(6-x)=4(3-2x) `
`<=>5-6+x=12-8x`
`<=>x+8x=12-5+6`
`<=>9x=13`
`<=>x=13/9`
`e, 4(x+3)=-7x+17 `
`<=>4x+12=-7x+17`
`<=>4x+7x=17-12`
`<=>11x=5`
`<=>x=5/11`
`f, 5(x-3) - 4=2(x-1)+7`
`<=>5x-15-4=2x-2+7`
`<=>5x-2x=15+4-2+7`
`<=>3x=24`
`<=>x=8`
`g, 5(x-3)-4=2(x-1)+7 `
`<=>5x-15-4=2x-2+7`
`<=>5x-2x=15+4-2+7`
`<=>3x=24`
`<=>x=8`
`h,4(3x-2)-3(x-4)=7x+20`
`<=>12x-8-3x+12=7x+20`
`<=>12x-3x-7x=20+8+12`
`<=>2x=40`
`<=>x=20`
1/ Suy ra: -35 + 7x - 2x + 20 = 15
5x - 15 = 15
5x = 30
x = 6
2/ Suy ra: 4x - 20 - 3x - 21 = -19
x - 41 = -19
x = 22
3/ Suy ra: 8 - 4x + 3x - 15 = 14
-7 -x = 14
x = -7 -14
x = -21
4/ Suy ra: 7x - 63 - 30 + 5x = -6 + 11x
7x + 5x - 11x = -6 +63 + 30
x = 87
5/ Suy ra: -21x +35 + 14x - 28 = 28
-21x + 14x = 28 +28 - 35
-7x = 21
x= -3
6/ Suy ra: 20 - 5x + 7x - 14 = -2
2x = -8
x = -4
7/ Suy ra: 4x +15 -5x = 7
-x = -8
x = 8
8/ Suy ra: 5x - 35 +30 -10x = 20
-5x - 5 = 20
-5x = 25
x = -5
9/ Suy ra: 35 - 7x + 5x - 10 = 15
-7x + 5x = 15 +10 - 35
-2x = -10
x = 5
20) -5-(x + 3) = 2 - 5x ⇔ -5 - x - 3 = 2 -5x ⇔ 4x = 10 ⇔ x = \(\frac{5}{2}\)
Vậy...
a ) \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{4}{35}-\frac{\left(-11\right)}{70}\right|\)
=> \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{4}{35}+\frac{11}{70}\right|\)
=> \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{19}{70}\right|\)
=> \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\frac{19}{70}=\frac{3}{35}\)
=> \(\frac{2}{5}+x+\frac{3}{2}=\frac{3}{7}-\frac{3}{35}=\frac{12}{35}\)
=> \(\frac{2}{5}+x=\frac{12}{35}-\frac{3}{2}=-\frac{81}{70}\)
=> \(x=-\frac{81}{70}-\frac{2}{5}=-\frac{109}{70}\)
b) \(\frac{3}{4}\left(x-8\right)=\frac{5}{7}\left(4-\frac{1}{2}\right)\)
=> \(\frac{3}{4}x-6=\frac{5}{2}\)
=> \(\frac{3}{4}x=\frac{17}{2}\)
=> \(x=\frac{17}{2}:\frac{3}{4}=\frac{34}{3}\)
Câu c,d tự làm nhé
a. \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{4}{35}-\frac{-11}{70}\right|\)
\(\Rightarrow\frac{3}{7}-\left(\frac{19}{10}+x\right)=\frac{5}{14}-\left|\frac{4}{35}+\frac{11}{70}\right|\)
\(\Rightarrow\frac{3}{7}-\frac{19}{10}-x=\frac{5}{14}-\left|\frac{19}{70}\right|=\frac{5}{14}-\frac{19}{70}\)
\(\Rightarrow-\frac{103}{70}-x=\frac{3}{35}\)
\(\Rightarrow x=-\frac{103}{70}-\frac{3}{35}\)
\(\Rightarrow x=-\frac{109}{70}\)
b. \(\frac{3}{4}\left(x-8\right)=\frac{5}{7}\left(4-\frac{1}{2}\right)\)
\(\Rightarrow\frac{3}{4}\left(x-8\right)=\frac{5}{7}.\frac{7}{2}=\frac{5}{2}\)
\(\Rightarrow x-8=\frac{10}{3}\)
\(\Rightarrow x=\frac{34}{3}\)
c. \(\frac{3}{2}-4\left(\frac{1}{4}-x\right)=\frac{2}{3}-7x\)
\(\Rightarrow\frac{3}{2}-1+4x=\frac{2}{3}-7x\)
\(\Rightarrow\frac{1}{2}=\frac{2}{3}-7x-4x=\frac{2}{3}-11x\)
\(\Rightarrow11x=\frac{2}{3}-\frac{1}{2}=\frac{1}{6}\)
\(\Rightarrow x=\frac{1}{66}\)
d. \(4\left(\frac{1}{2}-x\right)-5\left(x-\frac{3}{10}\right)=\frac{7}{4}\)
\(\Rightarrow2-4x-5x+\frac{3}{2}=\frac{7}{4}\)
\(\Rightarrow2-9x=\frac{1}{4}\)
\(\Rightarrow9x=\frac{7}{4}\)
\(\Rightarrow x=\frac{7}{36}\)